2022
DOI: 10.3389/fpubh.2022.924025
|View full text |Cite
|
Sign up to set email alerts
|

Big data-driven intelligent governance of college students' physical health: System and strategy

Abstract: With the development of information technology, the application of a new generation of information technologies, such as big data, Internet Plus, and artificial intelligence, in the sports field is an emerging, novel trend. This paper examined the relevant research results and literature on physical education, computer science, pedagogy, management, and other disciplines, then used a self-made questionnaire to investigate the physical health status of Chinese college students. The big data were subsequently an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For instance, Guo notes that by doing a thorough examination of player movement data, coaches get the ability to discern the particular strengths and shortcomings of individual players [2]. Equally, Deng et al report that a detailed comprehension of this information allows for developing training sessions tailored to address unique requirements and promote a more encouraging and all-encompassing atmosphere [3]. The transition towards personalized training recognizes and appreciates the varied abilities within a group of teenage athletes, fostering a comprehensive and all-encompassing approach to the growth of each athlete.…”
Section: Training Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Guo notes that by doing a thorough examination of player movement data, coaches get the ability to discern the particular strengths and shortcomings of individual players [2]. Equally, Deng et al report that a detailed comprehension of this information allows for developing training sessions tailored to address unique requirements and promote a more encouraging and all-encompassing atmosphere [3]. The transition towards personalized training recognizes and appreciates the varied abilities within a group of teenage athletes, fostering a comprehensive and all-encompassing approach to the growth of each athlete.…”
Section: Training Methodologiesmentioning
confidence: 99%
“…Big data overcomes regional biases, guaranteeing a more comprehensive approach to identifying talent. An example of this is the Moneyball phenomenon in baseball, as Deng et al emphasized, which demonstrated how data-driven analysis enabled the Oakland Athletics to find players who were not recognized for their true value [3]. This approach challenged traditional scouting beliefs and encouraged a more diverse selection of players.…”
Section: Talent Identificationmentioning
confidence: 99%
“…The information ecological chain theory, introduced in the 1980s, focuses on the interconnectedness of information flow among various information subjects in information systems [45,46]. Analysis shows that the application scenarios based on this theory involve information flow activities among three types of information subjects: information generators, information disseminators, and information consumers.…”
Section: Construction Of the Ugc Short Video Value Assessment Index S...mentioning
confidence: 99%
“…In addition to being in charge of teaching science (Avery & Meyer, 2012;Kind, 2016), teachers also play a role in shaping a conducive academic climate (Chan-Anteza, 2020;Iurea, 2015;Kutsyuruba et al, 2015;Mansor et al, 2021). Teachers who lead learning not only have the responsibility to impart knowledge but also play a role in creating a school ecosystem that supports the wellbeing of all members of the school community (Deng et al, 2022;Kutsyuruba et al, 2015;Roffey, 2012).…”
Section: Introductionmentioning
confidence: 99%